2012
DOI: 10.1002/ijc.27965
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for elimination of gastric cancer deaths in Japan

Abstract: We explore a strategy for the elimination of gastric cancer deaths in Japan. Most gastric cancer is due to H. pylori infection in Japan. The effect of H. pylori eradication therapy on gastric cancer prevention in younger people is excellent, but it declines along with advancing age. Therefore, a test-and-treat approach to H. pylori infection is recommended in younger people, while for people aged 50 years or older a combination of countermeasures for H. pylori eradication that includes primary prevention and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
89
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 25 publications
1
89
0
5
Order By: Relevance
“…Our study of patients in Bangladeshi observed high H. pylori resistance rates to CAM and MNZ (39.3% and 94.6%), which are currently recommended as first-line therapeutics in many Asian countries [2][3][4][5]. CAM resistance has been shown to be associated with any one of three well-known point mutations in the 23S ribosomal RNA (rRNA) gene of H. pylori; these three mutations are responsible for more than 90% of CAM resistance cases in developed countries [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study of patients in Bangladeshi observed high H. pylori resistance rates to CAM and MNZ (39.3% and 94.6%), which are currently recommended as first-line therapeutics in many Asian countries [2][3][4][5]. CAM resistance has been shown to be associated with any one of three well-known point mutations in the 23S ribosomal RNA (rRNA) gene of H. pylori; these three mutations are responsible for more than 90% of CAM resistance cases in developed countries [16].…”
Section: Discussionmentioning
confidence: 99%
“…First-line, alternative first-line, second-line, and even third-line therapies for H. pylori eradication have been proposed. According to current guidelines, a triple therapy containing a proton pump inhibitor and two antibiotics, amoxicillin (AMX) and clarithromycin (CAM) or metronidazole (MNZ), remains the standard first-line regimen for treatment of H. pylori infection [2][3][4][5]. However, in recent years, the efficacy of these legacy triple regimens has been seriously challenged and eradication rates below 70% have been reported in many countries [6].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is a real need to develop appropriate screening strategies for its early detection. In Japan, one of the countries with the highest incidence of gastric cancer, strategies that include the eradication of H. pylori among young people and periodic endoscopic examination have been proposed to reduce gastric cancer deaths (5). However, endoscopy is an invasive and a costly method that requires special equipment and well-trained personnel to offer reliable diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer is often diagnosed at an advanced stage and consequently carries a poor prognosis (3). Importantly, if it is detected at an early asymptomatic stage, it can be curable (4); for example, in Japan, a country with the highest incidence of gastric cancer, nation-wide strategies based on improved tests for detection of early gastric cancer or precancerous lesions have decreased the incidence of gastric cancer and increased survival rate (5).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence suggests that H. pylori is a major factor in the development of gastric cancers, thus its eradication will be a main preventive strategy of gastric cancer. 2 This microorganism, however, is difficult to culture in vitro. Blood or serum added to media is recommended for maximizing the success of the culture; thus, various agar media containing bovine blood or serum have been used to cultivate H. pylori.…”
Section: Introductionmentioning
confidence: 99%